Enhanced clustering routing protocol for power-efficient gathering in wireless sensor network - Hussaini, Mukhtar; Bello-Salau, Habeeb; Salami, Abdulazeez F; Anwar, Farhat; Hassan Abdalla Hashim, Aisha; Islam, Md Rafiqul (Kohat University of Science and Technology (KUST), Pakistan, 2012)
Wireless sensor network (WSN) is a new and fast advancing technology, which is opening up many opportunities in the field of remote sensing and data monitoring. In spite of the numerous applications of WSN, issues related to determining a suitable and accurate radio model that will foster energy conservation in the network limit the performance of WSN routing protocols. A number of radio models have been proposed to address this issue. However, the underlying assumptions and inaccurate configuration of these radio models make them impractical and often lead to mismanagement of scarce energy and computational resources. This paper addresses this problem by proposing an enhanced radio model that adapts to the frequent changes in the location of the sensor nodes and is robust enough to report reliable data to the base station despite fluctuations due to interference. The impact of incorporating stepwise energy level and specialized data transmission schemes in the proposed radio model is also investigated in this paper. The performance of the proposed radio model is evaluated using OMNET++ and MATLAB and the results obtained is benchmarked against PEGASIS. It is shown by simulation that the novel LEACH-IMP performs better with respect to energy consumption, number of links faults, number of packets received, signal attenuation, and network lifetime.